FBP : Federal Bureau of Physics. Vol. 1, The Paradigm Shift - Oliver, Simon, 1969- (DC Comics/Vertigo, 2014)
"Wormholes in your kitchen. Gravity failures at school. Quantum tornadoes tearing through the midwest. As with all natural disasters, people do what they always do: They adapt and survive. And if things get really bad, the Federal Bureau of Physics (FBP) is only a call away. FBP: Federal Bureau of Physics is the story of Adam Hardy: Young, brash and smart, he's a rising star at the FBP, but when a gravity failure leads to the creation of an alternate dimension known as a "BubbleVerse," Adam is sent on a rescue mission and finds his skills and abilities pushed to their limits when he discovers his partner has a different agenda... Collects issues #1-7"--